The Effectiveness of Problem-Based Learning in Enhancing High School Students' Conceptual Understanding of Waves: Descriptive-Analytical Literature Review - Yesika Ayunil Mudhinun; Dinda Miftahul Jannah; Reni Urbaningrum; Lulu Agustina (Indonesian, 2026)
Physics learning often faces challenges where wave concepts are considered abstract, leading to low student understanding and misconceptions. This research aims to examine the effectiveness of Problem-Based Learning (PBL) in enhancing high school students' conceptual understanding of waves. Using a descriptive-analytical literature review, this study analyzed 25 relevant journal articles published between 2017 and 2026. The findings indicate that PBL consistently improves conceptual understanding, critical thinking, and problem-solving skills compared to conventional methods. The model's effectiveness is optimized through digital technology integration, such as virtual laboratories (PhET) and interactive electronic modules (E-LKPD), which facilitate complex phenomenon visualization. Furthermore, teacher-provided scaffolding is essential to guide students through authentic investigations. The study concludes that the integration of PBL with digital media serves as an effective pedagogical strategy to improve science literacy and physics learning quality in secondary education. This review provides empirical evidence and serves as an innovative reference for educators in designing adaptive learning strategies for the 21st-century classroom.